Foreign Experience of Implementing Electronic Commerce Systems in Joint-Stock Companies and Its Practical Significance - Nozimov Eldor Anvarovich (International Journal on Economics, Finance and Sustainable Development, 2025)
The practical relevance of implementing electronic commerce systems in joint-stock firms abroad is discussed in this article, along with the key tactics and methods that Uzbekistan might employ to effectively compete in international electronic commerce marketplaces. Even more crucial to the nation's economy is the growth of internet commerce. According to New Uzbekistan's Development Strategy for 2022–2026, electronic commerce will play a major role in the digital economy, which is intended to become the primary "driver" of economic development and grow by at least 2.5 times. Based on the author's research, the article provides information on how Uzbek businesses may successfully leverage international markets and collaborate with new clients and marketplaces.